Investigating the impact of Organizational Citizenship Behavior on Supply Chain Performance and Corporate Sustainability: an empirical study - Muhammad Khan; Alisher Tohirovich Dedahanov; Yasmina Khadir; Rakhmonov Dilshodjon Alidjonovich; Kurbanbekova Mohichehra Turobjonovna; Obiddin Toshmurzaevich Yuldashev; Imomov Jamshidxon Odilovich (Cogent Business & Management)
This study empirically examines the influence of six dimensions of Organizational Citizenship Behavior (OCB) on Supply Chain Performance (SCP) and subsequently, Corporate Sustainability (CS). Anchored in social exchange theory, it proposes a conceptual model delineating how six OCB dimensions – Civic Virtue, Organizational Loyalty, Courtesy, Helping Behavior, Sportsmanship and Conscientiousness – independently affect SCP and mediate CS outcomes. Utilizing partial least squares structural equation modeling (PLS-SEM) via SmartPLS version 3.3.6 software, data from 441 SC professionals across diverse industries were analyzed through snowball sampling. Results show that each OCB dimension significantly enhances SCP; Civic Virtue, Organizational Loyalty and Courtesy notably boost teamwork and productivity; Helping Behavior and Sportsmanship foster a supportive SC environment; Conscientiousness ensures operational reliability. Moreover, SCP positively influences CS, confirming its mediating role between OCB dimensions and CS achievements. The study underscores the importance for companies to foster OCB elements to augment SCP for achieving CS objectives. This work contributes novel empirical insights into the substantial influence of OCB on SCP with cascading effects on CS – an area previously unexplored empirically.